Assemblies of Polyacrylonitrile-Derived Photoactive Polymers as Blue and Green Light Photo-Cocatalysts for Cu-Catalyzed ATRP in Water and Organic Solvents - Sun, Mingkang; Lorandi, Francesca; Yuan, Rui; Dadashi-Silab, Sajjad; Kowalewski, Tomasz; Matyjaszewski, Krzysztof (Frontiers in Chemistry, 2021)
Photoluminescent nanosized quasi-spherical polymeric assemblies prepared by the hydrothermal reaction of polyacrylonitrile (PAN), ht-PLPPAN, were demonstrated to have the ability to photo-induce atom transfer radical polymerization (ATRP) catalyzed by low, parts per million concentrations of CuII complex with tris(2-pyridylmethyl)amine (TPMA). Such photoinduced ATRP reactions of acrylate and methacrylate monomers were performed in water or organic solvents, using ht-PLPPAN as the photo-cocatalyst under blue or green light irradiation. Mechanistic studies indicate that ht-PLPPAN helps to sustain the polymerization by facilitating the activation of alkyl bromide species in two modes: (i) green or blue light-driven photoreduction of the CuII catalyst to the activating CuI form, and (ii) direct activation of dormant alkyl bromide species which occurs only under blue light. The photoreduction of the CuII complex by ht-PLPPAN was confirmed by linear sweep voltammetry performed under illumination. Analysis of the polymerization kinetics in aqueous media indicated even though CuI complexes comprised only 1-1.4% of all Cu species at equilibrium, they exhibited high activation rate constant and activated the alkyl bromide initiators 5-6 orders of magnitude faster than ht-PLPPAN.